"Get Up, Stand Up, Stand Up for Your Rights!" The Jamaicanization of Youth Across 11 Countries Through Reggae Music?. (May 2016) - Ferguson, Gail M.; Boer, Diana; Fischer, Ronald; Hanke, Katja; Ferreira, Maria Cristina; Gouveia, Valdiney V.; Tekman, Hasan Gürkan; Chang, Andrew; Pilati, Ronaldo; Bond, Michael H.; Adams, Byron G.; de Garay Hernández, Jimena; et al.
We investigated whether Reggae preferences are associated with similar values across cultures compared with its culture of origin—Jamaica. Remote acculturation predicts that Reggae listeners across countries will share similar cultural values with Reggae listeners in Jamaica regardless of their cultural or geographical distance from the Caribbean island. We analyzed the correlations between preferences for Reggae music and Schwartz's 10 value types in university student samples from Jamaica and 11 other societies in Europe, South America, Africa, and Asia (total N = 2, 561). In Jamaica, preferences for Reggae music were most strongly correlated with openness to change values and self-enhancement values. Across the other cultures, openness to change was the value dimension most strongly correlated with Reggae preference. Results also indicate some variations in Reggae's value associations and its similarity to the culture of origin. Reggae's value associations were more similar to Jamaica's in samples that are closer culturally in terms of Individualism/Collectivism scores, and closer geographically in terms of kilometers. In sum, results provide some support for remote value acculturation via Reggae listening across countries (i.e., "Jamaicanization") moderated by cultural and geographical proximity.